Breastfeeding and obesity at 21 years: a cohort study - Shields, Linda; Mamun, A.; O'Callaghan, M.; Williams, G.; Najman, J. (Blackwell Publishing, 2010)
To determine the influence of breastfeeding on overweight and obesity, as determined by body mass index in early adulthood. Obesity is a contemporary epidemic and linked to increased risk of later cardiovascular disease and type 2 diabetes. The success of long-term treatment is modest. Protective factors, such as potentially, and breastfeeding, are few and very important. There are uncertainties as to whether breastfeeding has a protective effect, especially in adults, or whether it is a reflection of other markers of obesity that are more linked to cardiovascular disease and atherosclerosis. Data were available for 2553 young adults. In neither the unadjusted or adjusted analysis was longer duration of breastfeeding associated with reduction in obesity in 21 years.Findings of this investigation are consisten with breastfeeding not independently affecting body mass index in young adults. Breastfeeding has a range of important benefits for infants, mothers and families, although duration of breastfeeding may not play a substantial role in preventing adult onset obesity.